Implementation of Copras Method for Decision Support Systems in Determining Purwakarta Tourist Destinations - Gito, Mochzen; Muhyidin, Yusuf; Wibawa Pratama, Ariya; Defriani, Meriska (RISTEC : Research in Information Systems and Technology, 2024)
Purwakarta Regency has a variety of interesting tourist destinations, but the large number of choices often makes it difficult for tourists to determine the location that suits their preferences. This research aims to build a web-based decision support system (SPK) with the Complex Proportional Assessment (COPRAS) method to help select the best tourist destinations. The research methods include problem identification, literature study, data collection, implementation of the COPRAS method, and system testing. The criteria used in the evaluation process include cost, distance, tourist facilities, operating hours, accessibility, and reviews of digital maps. The results of the implementation of the COPRAS method show that Panenjoan Village is the destination with the highest ranking with a value of 1,000. This system can make it easier for tourists to choose a destination that suits their needs